2021
DOI: 10.1371/journal.pone.0247337
|View full text |Cite
|
Sign up to set email alerts
|

Quality testing of veterinary antimicrobial products used for livestock in Vietnam, 2018–2019

Abstract: Access to quality veterinary antimicrobial products contributes to efficient treatment of diseases in Vietnamese livestock and to reducing antimicrobial resistance (AMR). Poor quality antimicrobial drugs can lead to treatment failure, potentially influencing the inappropriate use of antimicrobials products, including increasing the dose, combining drugs, or changing to a broader spectrum antimicrobial. The objective of the study was to determine the actual concentration of antimicrobial active ingredient (AAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The global veterinary medicine market expected to reach $85,059.4 million by 2030 [ 8 ]. Though veterinary medicines are one of the critical elements in improving productivity of livestock, informal pharmaceutical supply chains and illegal marketing, poor-quality medicines, medicines misuse and inappropriate use are prevailing factors [ 9 11 ], that could contribute to treatment failure, antimicrobial resistance development and economic losses [ 12 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global veterinary medicine market expected to reach $85,059.4 million by 2030 [ 8 ]. Though veterinary medicines are one of the critical elements in improving productivity of livestock, informal pharmaceutical supply chains and illegal marketing, poor-quality medicines, medicines misuse and inappropriate use are prevailing factors [ 9 11 ], that could contribute to treatment failure, antimicrobial resistance development and economic losses [ 12 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in Vietnam, analysis of veterinary antimicrobials indicated that among the 144 samples analyzed, about 91% met the national quality standard. Ten antimicrobials (6.9%) contained less than half the concentrations of the labeled content (8). With regard to the inspection of veterinary drugs in Brazil, there is an important gap in MAPA's inspection bodies regarding the conformity assessment of products being marketed in the domestic market.…”
Section: Resultsmentioning
confidence: 99%
“…The Market Information Commission points out that antimicrobials rank third in representativeness by therapeutic class (13). In Brazil, among the first-generation cephalosporins, cephalexin (CEP) appears prominently in veterinary dermatological medicine and as the first choice in the treatment of skin infections (1)(2)(3)(4)(5)(6)(7)(8)(9). The supervision of veterinary medicines is the responsibility of the Ministry of Agriculture, Livestock and Supply (MAPA) (2).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is enough is doubtful, as agro-veterinary shops are traders who may be motivated by profits. Quality assurance of antimicrobials used in animals and human is a critical control point, which help in curbing AMR through assurances for potency and efficiency [32] and must be taken seriously. Antimicrobials were administered by farmers through injections while mixing with water and other liquids before administration was also a common delivery method.…”
Section: Farmersmentioning
confidence: 99%